Youth Suicide Prevention and Intervention Best Practices and Policy Implications - Ackerman, John P.; Horowitz, Lisa M. (SpringerBriefs in Psychology; Advances in Child and Family Policy and Practice, 2022)
This open access book focuses on the public health crisis of youth suicide and provides a review of current research and prevention practices. It addresses important topics, including suicide epidemiology, suicide risk detection in school and medical settings, critical cultural considerations, and approaches to lethal means safety. This book offers cutting-edge research on emerging discoveries in the neurobiology of suicide, psychopharmacology, and machine learning. It focuses on upstream suicide prevention research methods and details how cost-effective approaches can mitigate youth suicide risk when implemented at a universal level. Chapters discuss critical areas for future research, including how to evaluate the effectiveness of suicide prevention and intervention efforts, increase access to mental health care, and overcome systemic barriers that undermine generalizability of prevention strategies. Finally, this book highlights what is currently working well in youth suicide prevention and, just as important, which areas require more attention and support. Key topics include: The neurobiology of suicide in at-risk children and adolescents. The role of machine learning in youth suicide prevention. Suicide prevention, intervention, and postvention in schools. Suicide risk screening and assessment in medical settings. Culturally informed risk assessment and suicide prevention efforts with minority youth. School mental health partnerships and telehealth models of care in rural communities. Suicide and self-harm prevention and interventions for LGBTQ+ youth. Risk factors associated with suicidal behavior in Black youth. Preventing suicide in youth with autism spectrum disorder (ASD) and intellectual disability (ID). Youth Suicide Prevention and Intervention is a must-have resource for policy makers and related professionals, graduate students, and researchers in child and school psychology, family studies, public health, social work, law/criminal justice, sociology, and all related disciplines.